Paradigm change: a history of geography in the United States, 1892-1925. - Martin, G.J. (National Geographic Research, 1985)
The third of 5 paradigm periods posited for the history of American geography extends from the establishment of the Committee of Ten in 1892, to the publication of Carl Sauer's 'The Morphology of Landscape' in 1925. This period witnessed the emergence of discipline and profession - an inert physiography, energized by the discipline-forming Davisian cycle of erosion, preceded the causal notion. Determinisms that gave way to studies of control, adjustment, and the geographic factor, provided a framework for the geographic philosophies of such scholars as Albert Perry Brigham, Ellsworth Huntington, and Ellen Semple. Regional delimitations of physiographic provinces and variant forms of economic geography emerged as alternatives to causality. The geography of France, Germany, and Britain afforded little support for varieties of determinism in America, and was further questioned during the 1914-1918 war years. Meanwhile, Wellington D. Jones and Carl O. Sauer developed another viewpoint, adumbrated by Sauer in a series of papers culminating in 'The Morphology of Landscape'. The locus of American geography had been moved.-Author
Keywords: dept.egm; ⛔ No DOI found